2017
DOI: 10.1182/bloodadvances.2017010918
|View full text |Cite
|
Sign up to set email alerts
|

Somatic HLA mutations expose the role of class I–mediated autoimmunity in aplastic anemia and its clonal complications

Abstract: Acquired aplastic anemia (aAA) is an acquired deficiency of early hematopoietic cells, characterized by inadequate blood production, and a predisposition to myelodysplastic syndrome (MDS) and leukemia. Although its exact pathogenesis is unknown, aAA is thought to be driven by Human Leukocyte Antigen (HLA)-restricted T cell immunity, with earlier studies favoring HLA class II-mediated pathways. Using whole exome sequencing (WES), we recently identified two aAA patients with somatic mutations in HLA class I gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 57 publications
6
72
0
1
Order By: Relevance
“…In one study, about 3% to 4% of LOH in the HLA region has been reported among AML patients at diagnosis . In contrast, a somatic HLA loss caused by chromosome 6p LOH or HLA gene mutation was found in 17% of aplastic anemia . As a result of the search for HLA mutations in hematologic malignancies, in addition to LOH for all or part of one HLA haplotype on chromosome 6p, we identified 11 published cases with HLA somatic mutation: 3 acute myelogenous leukemia (AML) with A*02:01 , 1 AML with B*15:01 , 1 acute lymphoblastic leukemia (ALL) with A*03:01 , 1 ALL with A*24:02 , 1 ALL with B*39:01 , 1 chronic lymphocytic leukemia with B*07:02 , 1 non‐Hodgkin lymphoma (NHL) with B*35:01 , 1 NHL with DRB1*13:01 , 1 NHL with DQB1*03:01.…”
Section: The Results Of Hla‐drb1 Typing In the Patient And Sibling Donormentioning
confidence: 99%
“…In one study, about 3% to 4% of LOH in the HLA region has been reported among AML patients at diagnosis . In contrast, a somatic HLA loss caused by chromosome 6p LOH or HLA gene mutation was found in 17% of aplastic anemia . As a result of the search for HLA mutations in hematologic malignancies, in addition to LOH for all or part of one HLA haplotype on chromosome 6p, we identified 11 published cases with HLA somatic mutation: 3 acute myelogenous leukemia (AML) with A*02:01 , 1 AML with B*15:01 , 1 acute lymphoblastic leukemia (ALL) with A*03:01 , 1 ALL with A*24:02 , 1 ALL with B*39:01 , 1 chronic lymphocytic leukemia with B*07:02 , 1 non‐Hodgkin lymphoma (NHL) with B*35:01 , 1 NHL with DRB1*13:01 , 1 NHL with DQB1*03:01.…”
Section: The Results Of Hla‐drb1 Typing In the Patient And Sibling Donormentioning
confidence: 99%
“…Somatic HLA class 1 loss was correlated with a more severe disease course and more frequent evolution to MDS. In contrast to the findings in this report, previous other studies employing WES did not identify HLA class mutations probably due to lower‐sensitivity detection strategies employed in the latter . These recent findings further strengthen the role of HLA class I‐mediated autoimmunity in AA pathogenesis.…”
Section: Immunogenetics Of Immune Dysregulationmentioning
confidence: 99%
“…These recent findings further strengthen the role of HLA class I‐mediated autoimmunity in AA pathogenesis. Among the many identified HLA risk alleles, a version of the HLA‐B gene called HLA‐B*‐ 40:02 plays a critical role in AA pathogenesis . Lack of allele expression of HLA‐B* 40:02, either by loss of heterozygosity of 6p chromosome (6pLOH) or due to various SMs, allows for the escape of HSCs from the attack of cytotoxic T cells that are specific to autoantigens presented by the lacked HLA class I alleles.…”
Section: Immunogenetics Of Immune Dysregulationmentioning
confidence: 99%
“…The presence of even a subclinical PNH clone has been found to correlate with an improved response to IST [7579, 70]. In contrast to PNH, the prognostic impact of somatic HLA loss is less clear [71, 72], with emerging data suggesting that HLA loss may be best viewed as a marker of a higher immune pathogenicity of a patient’s inherited HLA alleles [74, 73]. …”
Section: Clonal Evolutionmentioning
confidence: 99%